PENELUSURAN POTENSI AKTIVITAS SITOTOKSIK FRAKSI KULIT BATANG TUMBUHAN FALOAK (Sterculia quadrifida R.Br) - Rollando Rollando; Siswadi Siswadi (Universitas Wahid Hasyim Semarang, 2016)
ABSTRACT People on Timor island use Faloak (Sterculia quadrifida R.Br.) bark as herbal remedy to cure diseases such as liver diseases, gastroenteritis and as stamina booster. This study aims to analyze the ability of anticancer fraction of faloak bark ethanol extract. The mashed bark of faloak plants extracted by maceration method using ethanol. The ethanol extract fractionated using preparative thin layer chromatography with mixture mobile phase which, chloroform, n-butanol, ethyl acetate with ratio (3: 4: 1,5). Chromatogram detected with visible light, UV254, UV366, and cerium sulfate reagent, then marked. Fraction obtained five fractions. Cytotoxic test against T47D cell and Vero cell conducted using MTT, IC50 and selectivity sndex (SI) used as an anticancer efficacy parameter. Fraction 4 showed moderate anticancer activity with IC50 of 21.89 μg/mL in T47D cell line. Keywords: Faloak bark, anticancer activiy, T47D cell line